2009
DOI: 10.1128/aem.02945-08
|View full text |Cite|
|
Sign up to set email alerts
|

Dispersion of Multidrug-Resistant Enterococcus faecium Isolates Belonging to Major Clonal Complexes in Different Portuguese Settings

Abstract: The population structure of 56 Enterococcus faecium isolates selected from a collection of enterococci from humans, animals, and the environment in Portugal (1997 to 2007) was analyzed by multilocus sequence typing. We identified 41 sequence types clustering into CC17, CC5, CC9, CC22 and CC94, all clonal lineages comprising isolates from different hosts. Our findings highlight the role of community-associated hosts as reservoirs of enterococci able to cause human infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 38 publications
5
42
1
1
Order By: Relevance
“…The clone is infrequently reported as a clinical strain and has been described as a chicken strain by Freitas et al (55). However, this ST was not found in the chickens in the present study.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The clone is infrequently reported as a clinical strain and has been described as a chicken strain by Freitas et al (55). However, this ST was not found in the chickens in the present study.…”
Section: Discussioncontrasting
confidence: 55%
“…The strains of ST29 and ST57 that were isolated from chickens in this study were also reported to be isolated from people in the community and from pigs in Brazil, France, Australia, and Belgium. ST29 and ST57 belong to CC9 that has been identified as a global chicken lineage complex (55).…”
Section: Discussionmentioning
confidence: 99%
“…Besides dispersal of animals in global markets, the selective pressure exerted by antibiotics (e.g., tetracyclines and ␤-lactams) or metals (e.g., copper) heavily used in veterinary medicine and husbandry may have contributed to the maintenance of VRE among swine farms and facilitated the horizontal transfer of conjugative plasmids to other enterococcal hosts (or other Grampositive species serving as intermediates in the processes of horizontal gene transfer). Similarly to that described for E. faecium CC5, widespread clones of the predominant human enterococcal lineage E. faecium CC17 or E. faecalis CC2 have been recovered from companion and farm animals (4,9,13,14).…”
Section: Discussionmentioning
confidence: 97%
“…ST132 is an SLV of ST18, a predominant clone of the CC17 polyclonal subcluster. Although ST132 is not a predominant CC17 clone, isolates belonging to the ST have been recovered from unrelated patients hospitalized in Portugal and Tanzania, and it has been associated with a nosocomial outbreak described in Spain during an 18-month period, suggesting potential transmissibility (14,39,43,53; http://efaecium.mlst.net).…”
Section: Thirty-two (31 E Faecium [Vrefm]; 1 E Faecalis [Vrefs])mentioning
confidence: 99%
See 1 more Smart Citation